2017
DOI: 10.3390/proteomes5030014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Proteome and Transcriptome Response in Potato (Solanum tuberosum L.) Leaves Following Potato Virus Y (PVY) Infection

Abstract: Plant diseases caused by viral infection are affecting all major crops. Being an obligate intracellular organisms, chemical control of these pathogens is so far not applied in the field except to control the insect vectors of the viruses. Understanding of molecular responses of plant immunity is therefore economically important, guiding the enforcement of crop resistance. To disentangle complex regulatory mechanisms of the plant immune responses, understanding system as a whole is a must. However, integrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 57 publications
2
36
1
Order By: Relevance
“…However, these observations are based on changes in transcript abundance. Translation between transcriptomics and proteomics data is not trivial, as transcriptomic data may not necessarily reflect protein abundance in these functional categories [93]. Recently, a proteomic analysis of potato ER response against PVY was published by Szajko et al where the authors showed that the stress-responsive proteins were the most abundant among the qualitative changes induced by PVY in the resistant genotype PW363 [56].…”
Section: Extreme Resistance Response: No Signs Of Battlementioning
confidence: 99%
“…However, these observations are based on changes in transcript abundance. Translation between transcriptomics and proteomics data is not trivial, as transcriptomic data may not necessarily reflect protein abundance in these functional categories [93]. Recently, a proteomic analysis of potato ER response against PVY was published by Szajko et al where the authors showed that the stress-responsive proteins were the most abundant among the qualitative changes induced by PVY in the resistant genotype PW363 [56].…”
Section: Extreme Resistance Response: No Signs Of Battlementioning
confidence: 99%
“…The mRNAs can still be detected when translation is inhibited, while they cannot be translated into corresponding proteins [56,57]. Our study found that CGMMV infection significantly affected the accumulation levels of many ribosomal proteins and translation initiation factors in watermelon fruits (Table S6), which played important roles in post-transcriptional regulatory mechanisms [24]. These ribosomal proteins could stabilize the formation of ribosome around the start codons as well as affect translation efficiency.…”
Section: Correlation Analysis Of Proteome and Transcriptome Datamentioning
confidence: 78%
“…Due to the limitations in the sensitivity of identification methods of present proteins, changes in abundance of some proteins were usually not detected [13,24]. Additionally, discrepancies between transcript and protein levels might originate from specific biological metabolic processes.…”
Section: Correlation Analysis Of Proteome and Transcriptome Datamentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-Seq has been used to find insights in several plant-virus interactions, including model plants such as Arabidopsis thaliana (Sun et al, 2016;Wu et al, 2016), plants of agronomical importance such as Oryza sativa (Blazquez et al, 2013;Wong et al, 2015), Zea mays (Chakrabarty et al, 2018), Manihot esculenta (Fang et al, 2014;Amuge et al, 2017;Anjanappa et al, 2018), Solanum tuberosum (Goyer et al, 2015;Stare et al, 2017) and tropical fruits such as C. papaya (Madroñero et al, 2018). However, to date (04-10-2019), a Google Scholar search, the NCBI PMC database, and the Web of Science using the queries "plant", "virus", "interaction", "transcriptome", "RNA-Seq", and "Colombia" with different combinations did not yield any results for plant-virus interactions research developed in Colombia.…”
Section: Ngs In Transcriptomics To Elucidate Plant-virus Interactionsmentioning
confidence: 99%